Small bowel intussusception due to T-cell lymphoma - Vértiz, Moisés (2007)
Female patient FPM, 53 year-old, housewife, born in Amazonas, Peru, resident in Lima since teenager, was admitted at Emergency room due to colicky abdominal pain and abdominal tumour about 8 x 5 x 5 cm, in mesogastric area, mobile and painful. She had vomiting in two opportunities and lost undetermined weight. During surgery we found terminal ileum intussuception into the ascending large bowel and a tumour mass in terminal ileum. Pathology report informed high degree of malignancy no-Hodgkin T-cell phenotype lymphoma.